Cost of Producing Processed Oranges in Southwest Florida in 2018/19 - Ariel Singerman (EDIS, 2020)
This 4-page fact sheet written by Ariel Singerman and published by the UF/IFAS Food and Resource Economics Department estimates the cost of production per acre for processed oranges grown in southwest Florida in 2018/19 based on a survey of southwest Florida growers. https://edis.ifas.ufl.edu/fe1077